2008
DOI: 10.1038/ni.1634
|View full text |Cite
|
Sign up to set email alerts
|

Autophagic control of listeria through intracellular innate immune recognition in drosophila

Abstract: Autophagy, an evolutionally conserved homeostatic process for catabolizing cytoplasmic components, has been implicated in the elimination of intracellular pathogens during mammalian innate immune responses. However, the mechanisms underlying cytoplasmic infection-induced autophagy, and the role of autophagy in host survival against intracellular pathogens are unknown. Here we report that in drosophila, recognition of diaminopimelic acid-type peptidoglycans by the pattern recognition receptor PGRP-LE is crucial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
329
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 330 publications
(336 citation statements)
references
References 39 publications
(77 reference statements)
5
329
0
2
Order By: Relevance
“…85 Thus, a strong association between defective autophagy and impaired properties counteracting bacterial infections has been reported by numerous studies. 73,[86][87][88][89] However, a recent study has revealed a protective role of Atg16l1 deficiency against intestinal disease induced by the bacterial pathogen model, Citrobacter rodentium. This immunosuppressive role of ATG16L1 deficiency is dependent on the presence of NOD2 90 and adds to the complexity of the role of ATG16L1 in bacterial clearance.…”
Section: Atg16l1-dependent Signaling In Crohn Diseasementioning
confidence: 99%
“…85 Thus, a strong association between defective autophagy and impaired properties counteracting bacterial infections has been reported by numerous studies. 73,[86][87][88][89] However, a recent study has revealed a protective role of Atg16l1 deficiency against intestinal disease induced by the bacterial pathogen model, Citrobacter rodentium. This immunosuppressive role of ATG16L1 deficiency is dependent on the presence of NOD2 90 and adds to the complexity of the role of ATG16L1 in bacterial clearance.…”
Section: Atg16l1-dependent Signaling In Crohn Diseasementioning
confidence: 99%
“…Autophagy is classically activated in response to organelle damage and nutritional deficiency. This process is also involved in many host -bacterial interactions, notably in the clearance of the intracellular pathogen Listeria monocytogenes in Drosophila [74], and in the regulation of Wolbachia populations in nematodes, crustaceans and insects [75,76]. It also plays a critical role in the elimination of dinoflagellate symbionts in the sea anemone Aiptasia pallida [77,78].…”
Section: Cellular Processes Take the Lead Over Antimicrobial Peptidesmentioning
confidence: 99%
“…At distinct levels, autophagy contributes to both innate and adaptive immunity as a regulator and effector [84]. One autophagy effector function in innate immunity is xenophagy, which refers to the autophagy-dependent elimination of intracellular pathogens, including bacteria (S. pyogenes [85], S. flexneri [86], M. tuberculosis [87], S. typhimurium [88] and L. monocytogenes [89]), parasites (T. gondii [90]) and viruses (Herpes simplex virus [91]). In this way, autophagy restricts pathogen replication and survival, and inhibits pathogen-induced cell death in both plants and mice [92,93].…”
Section: Autophagy In Immunitymentioning
confidence: 99%